1987
DOI: 10.1093/nar/15.22.9365
|View full text |Cite
|
Sign up to set email alerts
|

Severe combined immune deficiency due to a homozygous 3.2-kb deletion spanning the promoter and first exon of the adenosine deaminase gene

Abstract: We have investigated the structural gene for adenosine deaminase (ADA) in a female infant with ADA deficiency associated severe combined immune deficiency (ADA-SCID) disease and her family by DNA restriction-fragment-length analysis. In this family a new ADA-specific restriction-fragment-length variant was detected, which involves a 3.2-kb deletion spanning the ADA promoter as well as the first exon. It was found that the patient, who was born to a consanguineous couple, was homozygous and both her parents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The size of the d'20" deletion (3,580 nucleotides) and the absence of terminal sequence homology are inconsistent with a direct error by DNA polymerase generating this deletion, as has been described for both procaryotic and eucaryotic deletions (1,9,22). Furthermore, the unique sequence of the DNA flanking the deletion termini appears to rule out an uneven crossing over between repetitive genomic elements, as suggested for spontaneous deletions in human P-globin, low-density lipoprotein receptor, adenosine deaminase, and growth hormone genes (3,5,28,38).…”
Section: Discussionmentioning
confidence: 92%
“…The size of the d'20" deletion (3,580 nucleotides) and the absence of terminal sequence homology are inconsistent with a direct error by DNA polymerase generating this deletion, as has been described for both procaryotic and eucaryotic deletions (1,9,22). Furthermore, the unique sequence of the DNA flanking the deletion termini appears to rule out an uneven crossing over between repetitive genomic elements, as suggested for spontaneous deletions in human P-globin, low-density lipoprotein receptor, adenosine deaminase, and growth hormone genes (3,5,28,38).…”
Section: Discussionmentioning
confidence: 92%
“…Six different mutations at the ADA locus have previously been precisely defined in children with ADA deficiency and SCID (13, [24][25][26][27]. We now report the first definition of a mutation that results in partial ADA deficiency in two unrelated children, both of whom express a heat-labile mutant ADA either alone or in combination with a second mutant ADA.…”
Section: Discussionmentioning
confidence: 94%
“…According to the predicted secondary structure, the two different mutations occur at either side of a seven-amino acid stretch with a beta configuration. Both represent loss of hydrophobic amino acids, but in the case of the mutation resulting in total deficiency of ADA and SCID the replacement is by a very polar basic amino acid that is predicted to result in a major increase in hydrophylicity (26)(27)(28), extending back into the beta structure and altering the site of transition to a turn. We have previously reported that there is an apparent increased prevalence of partial ADA deficiency in the Caribbean (2) that did not appear to reflect the spread ofa single mutation due to "founder effect" combined with a high coefficient of inbreeding.…”
Section: Discussionmentioning
confidence: 99%
“…1% of normal activity in blood mononuclear cells and B cell lines (complete deficiency) (6,9,10,13), the latter has 4-70% of normal activity (partial deficiency). Structural gene mutations, which presumably diminish enzyme stability or catalytic activity to different extents, occur in both groups (14)(15)(16)(17)(18)(19)(20)(21). The degree of ADA deficiency determines the severity of toxic effects of deoxyadenosine, including dATP pool expansion and inactivation of S-adenosylhomocysteine hydrolase.…”
Section: Introductionmentioning
confidence: 99%